Trustworthiness Perception and Decision to Conduct Transactions through E-Commerce Websites in Indonesia - Saragih, Ferdinand Dehoutman; Sinay, Doseba Tua (UI Scholars Hub, 2015)
The objective of this research paper is to examine the influence of internal and external schemes on both the trustworthiness perception and the purchasing decision of the consumers through digital media in Indonesia. The data collection is conducted through online survey of 392 respondents aged 18 or above who have at least conducted one online transaction. The collected data is analyzed using structural equation modeling (SEM) to examine the seven key hypotheses. The results of this study show how internal scheme (the aspects of how the message is transferred and consumer's knowledge) and external scheme (the aspects of the credibility of the e-commerce B2C websites, references and public comments) influence on the trustworthiness of the sites. Furthermore, this trustworthiness aspect influences the consumer's purchasing decision. However, only the external scheme that has a direct influence on consumer's purchasing decision. This study implies that e-commerce also contains elements of consumerism. It is recommended that online consumers realize, understand, able to refrain, and having the motivation to resist consumerism. In addition, the government needs to issue stricter regulations amid the online marketing efforts that are too aggressive and involve various types of the irresponsible external schemes.